2019
DOI: 10.1158/0008-5472.can-18-2603
|View full text |Cite
|
Sign up to set email alerts
|

CD317 Activates EGFR by Regulating Its Association with Lipid Rafts

Abstract: EGFR regulates various fundamental cellular processes, and its constitutive activation is a common driver for cancer. Anti-EGFR therapies have shown benefit in cancer patients, yet drug resistance almost inevitably develops, emphasizing the need for a better understanding of the mechanisms that govern EGFR activation. Here we report that CD317, a surface molecule with a unique topology, activated EGFR in hepatocellular carcinoma (HCC) cells by regulating its localization on the plasma membrane. CD317 was upreg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 46 publications
0
26
1
Order By: Relevance
“…For example, the long noncoding RNA, EGFR-AS1, was shown to directly binds EGFR mRNA, which promotes cell growth and metastasis through upregulating EGFR expression in renal cancer 44 . While a recent study has shown that CD317 is associated with lipid rafts, and activates EGFR in hepatocellular carcinoma (HCC) cells by regulating its localization on the plasma membrane 45 . In this study, we demonstrated that Foxq1 directly binds to the EGFR promoter region and regulates its transcription.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the long noncoding RNA, EGFR-AS1, was shown to directly binds EGFR mRNA, which promotes cell growth and metastasis through upregulating EGFR expression in renal cancer 44 . While a recent study has shown that CD317 is associated with lipid rafts, and activates EGFR in hepatocellular carcinoma (HCC) cells by regulating its localization on the plasma membrane 45 . In this study, we demonstrated that Foxq1 directly binds to the EGFR promoter region and regulates its transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the function of BST2-dependent MBR tethering might be important only in specific cell types (such as during the development of the brain, where MBRs accumulate at specific stages) 6 or in pathological conditions (such as in tumor cells, where BST2 is frequently found upregulated). 62,63 Altogether, we identified a striking common function of BST2 in retaining virions and MBRs at the plasma membrane. In both cases, BST2/tetherin limits their release into the extracellular medium and their spread to distant cells.…”
Section: Bst2 Localization At the Mbr Is Required For Promoting Mbr Amentioning
confidence: 77%
“… 13 Zhang et al found that CD317 activates EGFR in resistant progress as well. 14 To explore the resistance mechanism in depth and apply the possibility of EGFR targeted drugs, our research analyzed six HCC cell lines (Hep 3B2.1–7, Li-7, PLC/PRF/5, SK-HEP-1, SNU-182, SNU-387) for sensitivity to nimotuzumab. Then we compared the RNA-seq differences between sensitive and resistant group cell lines.…”
Section: Discussionmentioning
confidence: 99%
“… 9–12 Some studies showed that the complex signaling pathways are the primary cause of drug resistance in HCC cells. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation